(untitled) (Research, Society and Development, 2020)
In Brazil, Youth and Adult Education (EJA) is characterized by a series of state programs that aim, in a contingent way, to provide alternatives to formal schooling for those who failed to complete it at the proper age. According to the Base Document that guides the Program, the purpose of PROEJA is to provide the integral development of individuals so that they have full conditions to carry out their social activities and citizen practices. The objective of this work is to portray PROEJA students in RFEPCT from the 18,184 enrollments made in 2018 through the bounding categories Color / Race and Family Income and, also, Sex and Age Group of Students. The locus of data collection presented here was the Nilo Peçanha Platform (PNP), a virtual environment for the dissemination of information from RFEPCT (www.plataformanilopecanha.org). The data obtained reveal that this public is made up of a balanced number between men and women, mostly black and brown people of working age, however, from a low-income socio-economic reality.